In vivo Assessment of Antioxidant and Wound Healing Improvement of a New Schiff Base Derived Co (II) Complex in Rats - El-Ferjani R.M.; Ahmad M.; Dhiyaaldeen S.M.; Ibrahim M.Y.; Adam H.; Mohd Yamin B.; Al-Obaidi M.M.J.; Al Batran R.; Farah Wahida Harun (Nature Publishing Group, 2024)
Indexed by WOS/SCOPUS